2016
DOI: 10.21548/30-1-1421
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Induction of Ageing Character in Brandy Products – Part III. Influence of Toasting

Abstract: As part of a broader study that investigated techniques for the rapid induction of the needed ageing character in brandy products, the effect of oak wood toasting on quality and chemical composition of oak wood extracts and matured and unmatured pot-still brandy, is reported on. Extracts, prepared from oak chips supplied by a South African cooper, and from commercially obtained oak, and representing different oak types and levels of toasting (i.e. untoasted, light, medium and heavy), were added to 70% (v/v) un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 21 publications
1
7
1
Order By: Relevance
“…The sensory threshold of eugenol, a volatile phenol, is estimated at 0.011 mg/L in 10% ethanol and 0.050 mg/L in 20% ethanol (Singleton, 1995). Even after eight months' maturation, the concentrations of transoak lactone in this study (Van Jaarsveld et al, 2009a, 2009b, 2009c were generally below the reported thresholds for the trans form, i.e. about 0.8 mg/L (Singleton, 1995) and 0.067 mg/L (Otsuka et al, 1974).…”
Section: Figurecontrasting
confidence: 70%
See 4 more Smart Citations
“…The sensory threshold of eugenol, a volatile phenol, is estimated at 0.011 mg/L in 10% ethanol and 0.050 mg/L in 20% ethanol (Singleton, 1995). Even after eight months' maturation, the concentrations of transoak lactone in this study (Van Jaarsveld et al, 2009a, 2009b, 2009c were generally below the reported thresholds for the trans form, i.e. about 0.8 mg/L (Singleton, 1995) and 0.067 mg/L (Otsuka et al, 1974).…”
Section: Figurecontrasting
confidence: 70%
“…Only the 65% (v/v) concentration was considered in the statistical evaluation. 0.4045 sinapaldehyde) in unmatured and matured pot-still brandies were higher than those of the aromatic acids (vanillic and syringic acids) in this study (Van Jaarsveld et al, 2009a, 2009b, 2009c. The oak wood extracts prepared in this study therefore possess some of the chemical characteristics of spirits aged traditionally in barrels, conferring to pot-still brandies some distinctive properties of barrel-aged brandies.…”
Section: Figurementioning
confidence: 48%
See 3 more Smart Citations